Characterization of pneumonia incidence supported by a business intelligence system - Santos, Maribel Yasmina (2015)
Pneumonia, when talking about respiratory diseases, is the leading cause of death and hospital admissions in Portugal, following the global trend, as described by the World Health Organization, which state that is the leading infectious cause of death in children worldwide, accounting for 15% of all deaths of children under 5 years old and, also, that the lower respiratory infec- tions are among the 10 leading causes of death at a Mundial level. If at a worldwide level it is a serious concern, at a local level, country size, pneumonia has also shown an increase in its incidence over the last past decade. This paper presents the overall characterization of pneumonia in Portugal from 2002 to 2011, being possible to study its evolution, degree of fatality and, also, the geo- spatial distribution of the disease over the country. In this decade, a total of 369 160 patients were assisted in hospitals, being the corresponding data analyzed with the help of a Business Intelligence system implemented for the integration, storage and analysis of all the data collected in this study. Besides the informa- tion collected in the hospital units, demographic data collected in the 2011 Portugal census were also stored in the data warehouse, allowing the overall characterization of pneumonia and its incidence in the population.